Normative coherence for development and regionalism: Gender equality in ASEAN's migration policies. (24th March 2022) - Häbel, Sandra; Koff, Harlan; Adam, Marie
Summary: Motivation: The United Nations 2030 Agenda recognizes regions as important actors in implementing the sustainable development agenda. At the same time, regions are often criticized for lacking effective implementation, especially in relation to gender equality. Purpose: This study examines whether the Association of Southeast Asian Nations (ASEAN) implements its global commitment to gender equality at a regional level. Methods and approach: We apply qualitative analysis of key ASEAN documents in order to determine how gender equality is implemented regionally. We particularly focus on frameworks related to female migrant workers in ASEAN. Findings: The analysis shows that ASEAN is formally committed to improving gender equality at a regional level, however, female migrants often end up in unfavourable conditions and precarious work relationships without any institutionalized protection because ASEAN's gender equality initiatives are largely concentrated in the Cultural Community and absent from the Economic Community, indicating an absence of normative coherence for development with regard to gender equality. Policy implications: This limited impact of emerging regional commitments to gender equality arises from incoherences in ASEAN's normative governance framework which undermine normative coherence for development at the regional level.